As reformas da previdência no Brasil e o equilíbrio financeiro e atuarial dos Regimes Próprios de Previdência Social (RPPS), dos entes federados estaduais da Região Sudeste - Santos, Heliomar (2014)
The fiscal imbalance especially with respect to the welfare of civil servants in Brazil has led to constant search for solutions to ensure the funding of the model development. The changes implemented in the Reform of Social Security, have contributed significantly to reducing the accumulated pension liability over the years, mainly in the states, state capitals and other established before the promulgation of the 1988 Constitution.The states chosen for analysis showed mistakes, however there are promising results for the financial and actuarial balance of RPPS. Using models similar to those implemented in South America for public and private sector are presented in Brazil unsuitable for public servants. We need to continue to improve our knowledge seeking new alternatives that ensure the sustainability and viability of the system, without compromising the ability of investment of federal entities.